The Method of Fundamental Solutions for Solving Exterior Axisymmetric Helmholtz Problems with High Wave-Number (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we investigate the method of fundamental solutions(MFS) for solving exterior Helmholtz problems with high wave-numberin axisymmetric domains. Since the coefficient matrix in the linearsystem resulting from the MFS approximation has a block circulantstructure, it can be solved by the matrix decomposition algorithmand fast Fourier transform for the fast computation of large-scaleproblems and meanwhile saving computer memory space. Several numerical examples are provided todemonstrate its applicability and efficacy in two and threedimensional domains.